2013
DOI: 10.1038/onc.2013.542
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-associated CSF-1R binds to the promoter of proliferation-related genes in breast cancer cells

Abstract: The colony-stimulating factor-1 (CSF-1) and its receptor CSF-1R physiologically regulate the monocyte/macrophage system, trophoblast implantation and breast development. An abnormal CSF-1R expression has been documented in several human epithelial tumors, including breast carcinomas. We recently demonstrated that CSF-1/CSF-1R signaling drives proliferation of breast cancer cells via ‘classical' receptor tyrosine kinase signaling, including activation of the extracellular signal-regulated kinase 1/2. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…2 B ). Treatment with siCSF1R determined a decrease in CSF1R expression, in keeping with previous reports (25, 26). CSF1R silencing inhibited PGE2‐induced ERK1/2 phosphorylation with respect to control, nontargeting siRNA (Fig.…”
Section: Resultssupporting
confidence: 92%
“…2 B ). Treatment with siCSF1R determined a decrease in CSF1R expression, in keeping with previous reports (25, 26). CSF1R silencing inhibited PGE2‐induced ERK1/2 phosphorylation with respect to control, nontargeting siRNA (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Recently, Barbetti et al [238] reported nuclear translocation of the CSF-1R holoreceptor and its functions in breast cancer. They showed that nuclear CSF-1R was present only in breast cancer cells but not in fibroblasts or macrophages.…”
Section: Pdgfr Familymentioning
confidence: 99%
“…Immunofluorescence was performed as previously described. 41 Briefly, after fixation with 4% paraformaldehyde and permeabilization cells were incubated (overnight, 4 C) in PBS-1%…”
Section: Immunofluorescencementioning
confidence: 99%